ANALISIS KEABSAHAN DAN POTENSI NON-FUNGIBLE TOKEN SEBAGAI OBJEK JAMINAN FIDUSIA - Putri Azura Hana Haryadi (2023)
The development of information technology has pushed almost all areas of people's lives into something digital, especially in the field of trade. NFT is a digital asset whose popularity has skyrocketed in recent years. With works on NFTs, these NFT works should be used as objects of fiduciary guarantees. The problem of this research is how is the potential of NFT as an object of fiduciary guarantees and how is the validity of NFTs when used as objects of fiduciary guarantees. The normative juridical method is used with a statutory approach. The results of the study state that in the regulatory context, Indonesia has provided an opportunity or potential for NFTs as fiduciary guarantees originating from the Copyright Law. There are regulations in Indonesia that are related to making provisions when making NFT a fiduciary guarantee. This is a way to ensure that the imposition of fiduciary guarantees on NFTs remains in accordance with existing provisions and does not violate the law. This potential requires the addition of other regulations related to NFTs as objects of copyright. The position of NFT as an object of fiduciary guarantees is not specifically valid, nor is its legality. Based on the relevant regulations in force, there is potential for a legal product to be created or developed as a new additional regulation that regulates specifically and in detail. Utilization of NFTs needs to be accompanied by legal products and provisions that regulate specifically to provide protection from a legal perspective.